Detection of Two-Phase Slug Flow Film Thickness by Ultrasonic Reflection - Deddy Kurniadi; Narendra Kurnia Putra; Lalu Febrian Wiranata (Chaos Theory and Applications)
Slug flow is a common phenomenon in closed pipes, occurring in two-phase flow where liquid and gas phases mix, impacting the custody transfer or the efficiency of chemical reactions. This study aims to detect and analyze slug flow film thickness in two-phase flow, providing detailed structural flow information. The ultrasonic or Doppler reflection method is employed to identify slug flow and detect detailed thickness. Additionally, electrical resistance tomography (ERT) is used to image and confirm the presence of slug flow. A high-speed camera records the slug flow's shape in real time, validating its existence. The ultrasonic reflection method offers high accuracy, with a measurement error rate of less than 1% based on experimental results. The study uses a homogeneous block calibration method to measure slug flow thickness. Graphical results reveal clear differences between the slug flow regime, inner pipe wall, and outer pipe wall, with the first echo of slug flow being easily observable. The accuracy of results is attributed to the combination of FPGA (Field-Programmable-Gate-Array) instruments and measurement methods, showcasing the study's novel approach. This research introduces a new perspective or novelty on slug flow in multiphase flow studies, highlighting an innovative method for detecting film thickness.